Attendance Data Collection Using NFC Tags - Hutagalung, Gabriel Ardi; Dalimunte, Yulia Agustina; Khairina, Isni; Lubis, Muthi'ah Zahra; Firmansyah, Darma; Sinaga, Desi Natalia; Simanjuntak, Indah Sari; Indandi, Zanuar (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
In the field of contemporary wireless technology, near-field communication (NFC) stands out as an important force, enabling contactless transactions and the seamless exchange of information between electronic devices. This research explores the innovative integration of NFC into the attendance input process, which is linked to a website-based attendance system. NFC's adaptability, which was initially prominent in payment cards, has expanded across industries, empowering smartphones, tablets, and wearable devices. This study contributes to the ongoing development of NFC technology, proposing a renewable solution for student attendance systems. With a vision of increased efficiency, this research anticipates increased utilization of time and resources, thereby providing a promising path for the advancement of attendance management. Attendance tracking is a critical aspect of educational and organizational management, with traditional methods often plagued by inefficiencies and inaccuracies. This research explores the implementation of Near Field Communication (NFC) tags as a modern solution for attendance data collection. The study aims to assess the effectiveness of NFC technology in improving accuracy, efficiency, and real-time access to attendance information. The research employed a mixed-methods approach, incorporating a pilot study in an educational setting. NFC tags were distributed to participants, allowing for contactless attendance registration. Data was collected through observations, user feedback, and system logs. Additionally, a comparative analysis was conducted between NFC-based attendance tracking and traditional methods. Findings indicate a substantial improvement in accuracy and efficiency with NFC tags compared to traditional methods. Real-time data access provided administrators with up-to-the-minute attendance information, enabling timely interventions and streamlined record-keeping. User feedback highlighted the ease of use and convenience of the NFC-based system.